Ischemic and bleeding outcomes of triple therapy in patients on chronic anticoagulation undergoing percutaneous coronary intervention: A meta-analysis of randomized trials. (October 2019) - Dahal, Khagendra; Mustafa, Usman; Sharma, Sharan P; Apte, Nachiket; Bogabathina, Hari; Hanna, Magdy; Watti, Hussam; Azrin, Michael; Lee, Juyong; Mina, Goerge; Katikaneni, Pavan; Modi, Kalgi
Background: Triple therapy (TT) that includes oral anticoagulation and dual antiplatelet therapy is recommended in patients who are on chronic anticoagulation and undergo percutaneous coronary intervention (PCI). The randomized clinical trials (RCTs) comparing the effectiveness and safety of TT compared to double therapy (DT), which consists of an oral anticoagulation and one of the P2Y12 inhibitors, have shown increased risk of bleeding; however, none of the individual studies were powered to show a difference in ischemic outcomes. To compare the clinical outcomes of TT and DT, we performed this meta-analysis of RCTs. Methods: Electronic search of PubMed, EMBASE and Cochrane CENTRAL databases was performed for RCTs comparing TT and DT in patients who were on oral anticoagulation (Vitamin K antagonist or non-vitamin K antagonist oral anticoagulant) who underwent PCI. All-cause and cardiovascular mortality, myocardial infarction (MI), stroke, stent thrombosis (ST) and TIMI major and minor bleeding were the major outcomes. Results: An analysis of 5 trials including 10, 592 total patients showed that TT, compared to DT, resulted in non-significant difference in risk of all-cause [odds ratio (OR); 1.14;95% confidence interval (CI):(0.80–1.63); P = 0.46) and cardiovascular mortality [1.43(0.58–3.36); P = 0.44], MI [0.88 (0.64–1.21); P = 0.42], stroke [1.10(0.75–1.62); P = 0.63] and ST [0.82(0.46–1.45); P = 0.49]. TT, compared to DT resulted in higher risk of TIMI major bleeding [1.61(1.09–2.37); P = 0.02], TIMI minor bleeding [1.85(1.23–2.79); P = 0.003] and TIMI major and minor bleeding [1.81 (1.38–2.38); P < 0.0001; I 2 = 52%]. Conclusion: Compared to DT, the patients receiving TT are at a higher risk of major and minor bleeding with no survival benefit or impact on thrombotic outcomes.